Perfil hormonal da progesterona em ovelhas (Ovis aries) no início da gestação, no pré-parto e início da lactação - Rodrigues, P. A.; Vicente, WRR; Neto, J. C.; Oliveira, C. A. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1998)
The main objectives of this work were to determine the physiological patterns of progesterone on pregnancy and lactation in ewes, and to verify whether the hormone presents a 24h secretion rhythm. Serum levels of progesterone increased during gestation with an abrupt decrease by two days preterm. The autocorrelation analysis showed that this hormone, had a more evident circadian rhythm on preterm, than during early pregnancy and lactation.
Evaluation of progesterone hormone profile on ewes at early pregnancy, preterm and early lactation
Keywords: Progesterone; Circadian rhythm; ewe